PENGARUH SCARCITY MARKETING TERHADAP FOMO SERTA DAMPAKNYA TERHADAP DOOM SPENDING - Susinah Kuntadi; Teguh Iman Basuki (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2026)
This study examines the influence of Scarcity Marketing on FOMO (Fear of Missing Out) and its impact on Doom Spending. The theoretical framework used includes psychological reactance theory, which suggests that scarcity increases attractiveness; emotional regulation theory, which links shopping to emotional management; and Maslow's theory of needs, which emphasizes the need for self-actualization and belonging. The objectives of the study are to analyze the influence of Scarcity Marketing on FOMO, identify the relationship between FOMO and Doom Spending, and examine the simultaneous impact of Scarcity Marketing on Doom Spending through FOMO. This descriptive and verification study investigates three research variables: Scarcity Marketing, FOMO, and Doom Spending. The results of this study show that the Scarcity Marketing variable has a positive and significant influence on FOMO with a path coefficient of 0.348 and a P-value <0.001, the FOMO variable has a positive and significant influence on Doom Spending with a path coefficient of 0.577 and a P-value <0.001, the Scarcity Marketing variable has a positive and significant direct influence on Doom Spending with a path coefficient of 0.203 and a P-value <0.001, the Scarcity Marketing variable indirectly has a significant influence on Doom Spending through FOMO as a mediator